Organ donation after euthanasia. Review and criticism of foreign practice - O. N. Reznik (Вестник трансплантологии и искусственных органов, 2024)
This paper analyzes the problem of euthanasia, gives the history of this phenomenon, presents traditional ethical arguments for and against this practice, critically evaluates the practice of organ donation after euthanasia or euthanasia as a consequence of organ donation as established in some countries of the European Union, the US and Canada. The current status of this controversial practice is assessed.